Share Options, Share Award and Firm’s Performance: Evidence from Malaysian Public Listed Companies - Parij, Nur Azizah Mohamad; Abdullah, Wan Mohammad Taufik Wan (Financial Risk and Management Reviews, 2015)
The main intention of this paper is to examine the impact on firm’s performance once the directors are granted with the share options and share award. This study also intends to briefly identify the Shariah compliance impact towards the performance of firms that have granted the share options and share award. Earnings per share (EPS), Operating Cash Flow over Total Assets (OCFTA) and Tobin’s q used to examine seven hypotheses in this paper. The results exhibit share award presented better results in EPS and OCFTA. On the other hand the share options and the share award revealed significant relationship with Tobin’s q when Shariah compliance was included in the regression analysis model.